Kemampuan Mengidentifikasi Kelas Kata pada Novel “Mekkah Memoar Luka Seorang Tenaga Kerja Wanita (TKW) Karya Aguk Irawan MN” Siswa Kelas VIII SMP Unismuh Makassar - Hanana Muliana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The main problem in this study is to see how far the ability of class VIII students of SMP Unismuh Makassar in determining the class of words in the text of the novel